2007
DOI: 10.1021/je7002594
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Solubility of 3- and 4-Nitrophthalic Acids in Water

Abstract: The equilibrium solubility of 3- and 4-nitrophthalic acids in water was measured experimentally using Schreinemaker's wet residue method at temperatures ranging from (285.15 to 348.15) K at atmospheric pressure. The solubility of 3- and 4-nitrophthalic acids in water increased with the increase of temperature. The experimental solubility is correlated by an empirical equation. The calculated values via the empirical equation agreed well with experimental results for 3- and 4-nitrophthalic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The relationship between equilibrium solubility data of sodium 1-naphthalenesulfonate and temperature was correlated by modified Apelblat equation. The semiempirical equation was used as follows: …”
Section: Resultsmentioning
confidence: 99%
“…The relationship between equilibrium solubility data of sodium 1-naphthalenesulfonate and temperature was correlated by modified Apelblat equation. The semiempirical equation was used as follows: …”
Section: Resultsmentioning
confidence: 99%
“…A modified Apelblat equation used to correlate the connection between solubility of sodium 2,4-diaminobenzene­sulfonate and temperature, and the semiempirical equation presented as follows: ln ( x ) = A + B false( T / normalK false) + C nobreak0em0.25em⁡ ln ( T / K ) where A , B , and C are parameters, T is for the Kelvin temperature, and x is the solubility of the sodium 2,4-diaminobenzene­sulfonate in aqueous solutions of NaCl, Na 2 SO 4 , or C 2 H 5 OH in mole fraction. The C value reflects the effect of temperature on the fusion enthalpy, which is a deviation of heat capacity (Δ C p ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The results showed that the experimental data of 4-amino-4′-nitrodiphenyl sulfide solubility in n -butanol agree with the literature data well. The functional relationship of temperature and 4-amino-4′-nitrodiphenyl sulfide solubility in pure solvents is expressed by the modified Apelblat equation, which is a semiempirical equation stemming from the van’t Hoff equation ln ( x ) = A + B / ( T / K ) + C nobreak0em0.25em⁡ ln ( T / K ) where A , B , and C are adjustable empirical parameters, T is the Kelvin temperature, and x is the experimental mole fraction solubility of the 4-amino-4′-nitrodiphenyl sulfide.…”
Section: Resultsmentioning
confidence: 99%